Unraveling Darunaka (Dandruff): A Survey-Based Insight into its Psychosocial Impact - Bhusal, Elisha; Kumar Jajoriya, Vishnu; Kumar, Ravi; Choudhary, Sunita; Sharma, Akshay (International Research Journal of Ayurveda & Yoga, 2025)
Background: Dandruff, being a common condition with a global prevalence of 50% and a prevalence of 60.1% in South Asia, is not only an issue of physical symptoms. It influences the quality of life (QoL) of an individual suffering from it. Hence, to analyze the effect of this condition on the dermatological QoL of the affected person, this survey study has been conducted. This study incorporates the Dermatology Life Quality Index (DLQI) developed by the Department of Dermatology at Cardiff University, UK. Objectives: To assess the QoL of patients with dandruff and to perform a subclass analysis of the DLQI questionnaire. Methods: This quantitative, observational study was carried out in the Department of Swasthavritta and Yoga at the National Institute of Ayurveda, Jaipur, Rajasthan, India, from July 2024 until January 2025. Data were collected through a Google form using the validated English version of the Dermatology Life Quality Index (DLQI). Results: A total of 301 patients participated in the study. It was observed that 3% of the participants had an extremely large effect, 15% had a very large effect, 29% had a moderate effect, 26% had a small effect, and 27% had no effect of dandruff on their QoL. The mean DLQI of the participants was seen to be 6.42, with a minimum value of 0 and a maximum value of 30. Among the six subclasses, it was seen that dandruff affected symptoms and feelings the most, followed by daily activities, then treatment, then personal relationships, then work and school, and finally leisure. Conclusion: Dandruff (Darunaka) significantly affects the QoL, particularly in domains related to symptoms, emotional well-being, and daily activities. This survey-based study using the DLQI highlights the need for holistic management approaches that address both physical and psychosocial aspects of the condition. Ayurvedic insights offer valuable frameworks for personalized care, and further research is recommended to explore integrative treatment strategies.